When time matters: Mechanisms of change in a mediational model of foreign language playfulness and L2 learners’ emotions using latent change score mediation model - Kruk, Mariusz; Pawlak, Mirosław; Taherian, Tahereh; Yüce, Erkan; Shirvan, Majid Elahi; Barabadi, Elyas (Studies in Second Language Learning and Teaching, 2023)
In a dynamic system, time-dependent links between affective factors can provide more information than the level of response within a single isolated system. In the present study, influenced by the positive psychology movement and the complex dynamic systems theory in the domain of second language acquisition, first, we dealt with change in terms of short-term dynamics and long-term trajectories of foreign language enjoyment (FLE), foreign language boredom (FLB), and foreign language playfulness (FLP) in a sample of 636 learners of English as a foreign language (EFL) using univariant latent change score (LCS) models. Then, we explored the developmental processes involved in how changes in FLE and FLP were associated with changes in FLB. In particular, we tested mediation models to see whether the growth of FLP acts as a mediator between FLE and FLB changes in a multivariant LCS mediation (LCSM) model. The findings showed that (a) in a multivariant LCS model, FLE and FLP increases independently predicted decreases in FLB over time and (b) the growth of FLP acted as a mediator between variation in FLE and FLB. Participants showed interindividual and intraindividual divergences in their L2 emotions, not just on the first time of measurement, but also in short-term dynamics and long-term trajectories. The findings facilitate understanding of the complicated mechanism of variation in L2 emotions, thus potentially contributing to enhancement of pedagogical practices and learning outcomes.